Sleep, aging, and lifespan in Drosophila. - Bushey, D.; Hughes, K.A.; Tononi, G.; Cirelli, C. (BMC Neuroscience, 2010)
Epidemiological studies in humans suggest that a decrease in daily sleep duration is associated with reduced lifespan, but this issue remains controversial. Other studies in humans also show that both sleep quantity and sleep quality decrease with age. Drosophila melanogaster is a useful model to study aging and sleep, and inheriting mutations affecting the potassium current Shaker results in flies that sleep less and have a shorter lifespan. However, whether the link between short sleep and reduced longevity exists also in wild-type flies is unknown. Similarly, it is unknown whether such a link depends on sleep amount per se, rather than on other factors such as waking activity. Also, sleep quality has been shown to decrease in old flies, but it remains unclear whether aging-related sleep fragmentation is a generalized phenomenon.We compared 3 short sleeping mutant lines (Hk1, HkY and Hk2) carrying a mutation in Hyperkinetic, which codes for the beta subunit of the Shaker channel, to wild-type siblings throughout their entire lifespan (all flies kept at 20 degrees C). Hk1 and HkY mutants were short sleeping relative to wild-type controls from day 3 after eclosure, and Hk2 flies became short sleepers about two weeks later. All 3 Hk mutant lines had reduced lifespan relative to wild-type flies. Total sleep time showed a trend to increase in all lines with age, but the effect was most pronounced in Hk1 and HkY flies. In both mutant and wild-type lines sleep quality did not decay with age, but the strong preference for sleep at night declined starting in "middle age". Using Cox regression analysis we found that in Hk1 and HkY mutants and their control lines there was a negative relationship between total sleep amount during the first 2 and 4 weeks of age and hazard (individual risk of death), while no association was found in Hk2 flies and their wild-type controls. Hk1 and HkY mutants and their control lines also showed an association between total daily wake activity over the first 2 and 4 weeks of age and hazard. However, when both sleep duration and wake activity were used in the same regression, the effects of activity were much reduced, while most of the sleep effects remained significant. Finally, Hk1 flies and wild-type siblings were also tested at 25 degrees C, and results were similar to those at 20 degrees C. Namely, Hk1 mutants were short sleeping, hyperactive, and short lived relative to controls, and sleep quality in both groups did not decrease with age.Different Hk mutations affect the sleep phenotype, and do so in an age-dependent manner. In 4 of the 6 lines tested sleep associates significantly with lifespan variation even after any effect of activity is removed, but activity does not associate significantly with lifespan after the effects of sleep are removed. Thus, in addition to environmental factors and genetic background, sleep may also affect longevity. Sleep quality does not necessarily decay as flies age, suggesting that aging-related sleep fragmentation may also depend on many factors, including genetic background and rearing conditions.